Clearance kinetics and matrix binding partners of the receptor for advanced glycation end products. - Pavle S Milutinovic; Judson M Englert; Lauren T Crum; Neale S Mason; Lasse Ramsgaard; Jan J Enghild; Louis J Sparvero; Michael T Lotze; Tim D Oury (PLoS ONE, 2014)
Elucidating the sites and mechanisms of sRAGE action in the healthy state is vital to better understand the biological importance of the receptor for advanced glycation end products (RAGE). Previous studies in animal models of disease have demonstrated that exogenous sRAGE has an anti-inflammatory effect, which has been reasoned to arise from sequestration of pro-inflammatory ligands away from membrane-bound RAGE isoforms. We show here that sRAGE exhibits in vitro binding with high affinity and reversibly to extracellular matrix components collagen I, collagen IV, and laminin. Soluble RAGE administered intratracheally, intravenously, or intraperitoneally, does not distribute in a specific fashion to any healthy mouse tissue, suggesting against the existence of accessible sRAGE sinks and receptors in the healthy mouse. Intratracheal administration is the only effective means of delivering exogenous sRAGE to the lung, the organ in which RAGE is most highly expressed; clearance of sRAGE from lung does not differ appreciably from that of albumin.